Cost investment analysis in process industries with focus on occupational safety and health (osh) measures - Muhammad Muzaffar, Mat Lazim (2025)
Chemical processing plants face significant hazards due to the complexity of equipment such as oxo reactors, aldol reactors, hydrogenation reactors, and distillation columns. Ineffective design accuracy and inadequate safeguards often result in safety and economic risks. This study aims to enhance process safety by evaluating the existing design of a hypothetical process plant, identifying potential hazards through a pre-determined HAZOP study, and proposing engineering safety measures to address critical risks. A systematic methodology was adopted, starting with the evaluation of inaccuracies in the plant design, followed by an analysis of the current control systems. Engineering design-based safety measures were proposed as a secondary layer of protection, and their economic feasibility was assessed using a cost-benefit analysis (CBA). Equipment costs were calculated using the Turton 2009 formula, updated with contemporary CEPCI values, while safety measure costs were estimated using reliable online sources. The results indicate that the proposed safety measures significantly reduce operational risks and improve the economic sustainability of the plant. The CBA revealed a favourable cost-to-benefit ratio, demonstrating long-term financial benefits from safety investments compared to potential losses from unmitigated hazards. In conclusion, the study highlights the importance of integrating robust safety measures into process plant designs to achieve a balance between safety and economic viability, contributing to a safer and more sustainable chemical processing industry.